2006
DOI: 10.1097/01.brs.0000214895.67956.60
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of White Blood Cell Differential for Early Diagnosis of Surgical Wound Infection Following Spinal Instrumentation Surgery

Abstract: Lymphopenia represents immunodepression status, thus indicating the increased susceptibility to infection, which may lead to the development of postoperative infection. If lymphopenia is diagnosed as early as possible, surgical wound infection can be treated promptly without removing the instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 8 publications
3
81
0
Order By: Relevance
“…WBC count has been a less reliable indicator for infection. Takahashi et al [21] found that the most sensitive parameter for enhanced inflammation elicited by implants appears to be CRP because its level increased sharply immediately after surgery, reaching a high peak level on day two. The authors concluded that hardware was the cause of the acute inflammatory response with a high CRP level after surgery.…”
Section: Diagnosismentioning
confidence: 99%
“…WBC count has been a less reliable indicator for infection. Takahashi et al [21] found that the most sensitive parameter for enhanced inflammation elicited by implants appears to be CRP because its level increased sharply immediately after surgery, reaching a high peak level on day two. The authors concluded that hardware was the cause of the acute inflammatory response with a high CRP level after surgery.…”
Section: Diagnosismentioning
confidence: 99%
“…Biomarkers, such as elevated serum C-reactive protein (CrP), white blood cell (WBC) counts, and erythrocyte sedimentation rate (ESr) can assist in diagnosing deep subfascial infection, but often are not diagnostic. In adults with instrumented spinal fusion, CrP peaks at second postoperative day, and it may remain elevated for almost 6 weeks making differential diagnosis of systemic inflammatory response and deep surgical wound infection difficult (7)(8)(9)(10). Similarly, ESr peaks on fourth postoperative day and may remain elevated for 6 weeks after instrumented spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…And so, papers regarding postoperative control of fusion surgery have been published. Some detailed reports have been published regarding the inflammatory reactions that occur after spinal instrumentation surgery (Takahashi et al 2001(Takahashi et al , 2006. Other reports have addressed the issues of bleeding volume and anemia following posterior fusion surgery (Behrman and Keim 1992;Gause et al 2008).…”
mentioning
confidence: 99%